Evaluation of Liver Function Tests in Type2 Diabetic patients - Islam, M Akhtarul; Khan, MMR; Basak, PM; Khanam, MM; Bhattacharyya, PM (TAJ: Journal of Teachers Association, 2018)
This was a descriptive cross-sectional comparative study carried out in Department of Medicine, Rajshahi Medical College Hospital and Rajshahi Diabetic Association Hospital from July 2008 to June 2010. 100 (one hundred) diagnosed type2 diabetic patients and 30 apparently healthy people were included. All of those study population were free from taking any hepatoxic drugs and free from any preexisting liver disease. This exclusion was done by history, through clinical examination and relevant investigations. The prevalence of abnormal serum bilirubin, ALT, AST, Alkaline phosphatase, prothrombin time and S. albumin were 6%, 30%, 7%, 6%, 54% and 12% respectively in type2 diabetic patients and 00%, 3.3%, 00%, 6.7%, 10% and 3.3% respectively in normal people. All the LFTs of type 2 diabetic patients were mildly abnormal except 2 patients (2%) had moderate elevation of ALT, 7 patient (7%) had markedly prolonged PT, and 1 patient (1%) had moderately decreased s. albumin. In normal people all LFTs abnormalities were mild. TAJ 2016; 29(1): 21-23